Directions: Find values for a and b that will make the expressions equivalent, assuming that a does not equal b.

### Hint

### Hint

How does each base’s factors affect the equivalence?

### Answer

### Answer

There are two possible answers. One is when a and b are 2 and 4, giving 2^4 = 4^2. The other was found by Shashi and is when a and b are -2 and -4, giving (-2)^(-4) = (-4)^(-2).

Source: Owen Kaplinsky

-2, -4

Oh! I didn’t think of that!

I think have more answer like ;a=1,b=1 this is one answer:a=-1,b=-1

Unfortunately, this won’t work because it says that a cannot equal b.

Nice one! I’ll add it to the answers.